Qiyas dan Kemajuan Teknologi: Mengatasi Tantangan Etika dan Hukum Baru - Sabri; Ismail (Jurnal Indragiri Penelitian Multidisiplin, 2024)
This study aims to analyze the application of qiyas in responding to legal and ethical challenges arising from technological advancements. The method used is a reference study with a descriptive qualitative approach. The data type used is secondary data, obtained through a literature review of books, scholarly journals, and classical and contemporary Islamic legal documents discussing the concept of qiyas. Content analysis techniques are applied to identify key themes related to the application of qiyas in modern Islamic law.The findings show that qiyas has the potential to be a flexible method for addressing contemporary legal issues not specifically regulated in the Qur'an and Sunnah, such as bioethics and personal data protection. The application of qiyas in this context requires a deep understanding of relevant legal analogies and integration with other principles, such as maslahah (public interest) and istihsan (legal preference), to produce adaptive decisions.The study also finds that, while qiyas can be applied to some cases involving modern technology, there are limitations in interpreting the law on certain issues that require a renewal of approach. Therefore, it is recommended to adopt a more combinatory Islamic legal approach to maintain legal relevance in the digital era.